The issues on the commercialization of perovskite solar cells - Lixiu Zhang; Yousheng Wang; Xiangchuan Meng; Jia Zhang; Pengfei Wu; Min Wang; Fengren Cao; Chunhao Chen; Zhaokui Wang; Fu Yang; Xiaodong Li; Yu Zou; et al. (Materials Futures, 2024)
Perovskite solar cells have aroused a worldwide research upsurge in recent years due to their soaring photovoltaic performance, ease of solution processing, and low cost. The power conversion efficiency record is constantly being broken and has recently reached 26.1% in the lab, which is comparable to the established photovoltaic technologies such as crystalline silicon, copper indium gallium selenide and cadmium telluride (CdTe) solar cells. Currently, perovskite solar cells are standing at the entrance of industrialization, where huge opportunities and risks coexist. However, towards commercialization, challenges of up-scaling, stability and lead toxicity still remain, the proper handling of which could potentially lead to the widespread adoption of perovskite solar cells as a low-cost and efficient source of renewable energy. This review gives a holistic analysis of the path towards commercialization for perovskite solar cells. A comprehensive overview of the current state-of-the-art level for perovskite solar cells and modules will be introduced first, with respect to the module efficiency, stability and current status of industrialization. We will then discuss the challenges that get in the way of commercialization and the corresponding strategies to address them, involving the upscaling, the stability and the lead toxicity issue. Insights into the future direction of commercialization of perovskite photovoltaics was also provided, including the flexible perovskite cells and modules and perovskite indoor photovoltaics. Finally, the future perspectives towards commercialization are put forward.